How Hard are Accountants’ Jobs? - Iztok Kolar (Naše gospodarstvo/Our economy, 2012)
This paper investigates the characteristics of the accountant’s profession. The results of our research indicate that accountants are working more hours per week on average than typically worked in Slovenia and the 27 EU countries. The results of studying the absenteeism of respondents indicated that accountants take fewer sick leaves on average in Slovenia and the 27 EU countries. The collected data show that male accountants have no more of a taxing job than the opposite sex. The results of the exploratory factor analysis indicate the reasons for job efforts of the accounting profession; the great pressure inherent in their work, the lack of autonomy, and frequent changes of tasks and accounting rules. The greatest strains in the profession are caused by the great control at work and the rapid changes of state regulations and timelines for accountants’ tasks.